Determinants of profitability in Spanish financial institutions. Comparing aided and non-aided entities - Climent-Serrano, Salvador; Pavía, Jose M. (Journal of Business Economics and Management, 2015)
The last financial crisis has led to the greatest contribution of public funds ever made to Spanish banks. This paper studies why the need for support has been asymmetric, with not all of the institutions requiring aid. Based on profitability of assets (ROA), we determine using panel data econometric and logit response models the components of profit and loss accounts that generated profitability as well as the factors leading to some entities to ask for aid. The analyses show that before the beginning of the crisis there were significant differences between entities that needed aid and those that did not. The most profitable banks grounded their success in the traditional revenue components of financial institutions (such as margin on interest rates and commissions), as well as in revenues obtained from participated companies and extraordinary results. The model offers a tool to detect entities in difficulties in advance, reducing the financial and social costs of public interventions. The factors more impacting on profitability of Spanish institutions are also identified.